STUDENT PERSPECTIVE TOWARD ENERGY CONSERVATION IN UNIVERSITI UTARA MALAYSIA (Journal of Technology and Operations Management, 2024)
Climate change and global warming are crucial problems due to carbon dioxide (CO₂) emissions cause by fossil fuels consumption. Malaysia has a sustainable power mix but the industry and transportation sectors rely on fossil fuels to generate electricity. Energy conservation are important to improve or change the behavior of people in order to minimize energy usage because humans cannot longer rely on conventional energy sources. Due to the impact of climate change and global warning problems. The objectives of this study are (1) to determine the current practices of energy conservation among UUM students and (2) to investigate the relationship between current practices and energy conservation perspectives among UUM students. This study focuses on Universiti Utara Malaysia (UUM) students' academic session A221, which is semester 1 to semester 7 students. Researchers have used quantitative methods, the questionnaire was distributed using Google form that uploaded on social media and will receiving answers. A survey was conducted with 377 understudies to get information. The analysis was using statistical software package (SPSS) of software for using in data analysis. The results show the mean of attitude with total mean 31.87 is higher than the level of awareness, energy conservation knowledge and subjective norms, which mean that attitude is most influences perspective of students to energy conservation. Besides, the relationship between level of awareness, energy conservation knowledge, attitude and subjective norms are positive correlated. Based on the results and discussion, energy saving intervention strategies are proposed for student accommodation. Government should implement educational programs and campaigns to raise awareness toward energy conservation practice among students.